Lessons learned from nationwide perinatal audit of severe postpartum haemorrhage in the Netherlands - Lisa Broeders; Steven V Koenen; Nicole de Vocht; Thomas van den Akker; Ageeth N Rosman (International Journal for Quality in Health Care, 2026)
Abstract Background Severe postpartum haemorrhage (PPH) remains a leading and largely preventable cause of maternal morbidity and mortality worldwide. Delayed recognition, inappropriate fluid replacement, and suboptimal clinical management contribute to adverse outcomes. Clinical audit can identify deficiencies in care and stimulate quality improvement. In the Netherlands, a nationwide perinatal audit system enables multidisciplinary review of maternity care to enhance collaboration and optimize clinical practice. This study reports the first nationwide audit of severe PPH management in the Netherlands and aims to identify improvable care factors and draw lessons for clinical care. Methods In the Netherlands, perinatal audit is nationally coordinated and based on a set of periodic clinical themes. In 2020-2023, one such theme was severe PPH, defined as blood loss of ≥ 2500 ml in the first 24 hours after birth or blood loss requiring hysterectomy. Local multidisciplinary audit sessions were held within ‘perinatal cooperation groups’, comprised of maternity care professionals working with a region. During audit sessions, anonymized case reports were reviewed, and areas for improvement of clinical care were identified and documented. Audit findings were analysed quantitatively to group improvable care factors regarding clinical management provided to women sustaining severe PPH. In addition, narrative excerpts from audit reports were used descriptively to provide context to the findings. Results In 116 women sustaining severe PPH, audit revealed 234 improvable care factors, mostly related to non-adherence to guidelines and standards (47.8%), organisation of care (22.3%), and communication and documentation between care professionals and to patients (17.1%). Common issues included absence or ambiguity of local management protocols, unclear allocation of responsibilities among team members, limited capacity in terms of staffing and available labour rooms, and incomplete communication and documentation around referral between/within echelons. Nearly half of the improvable care factors were stated by local audit panellists to be likely or possibly associated with severe PPH. Conclusion Audit of PPH care revealed several areas for improvement in the Netherlands, including ensuring sufficient staffing and labour room capacity, and updating of national and local management protocols.